Impact of drug-eluting stent-associated coronary artery spasm on 3-year clinical outcomes: A propensity score matching analysis - Jabar Ali; Seung-Woon Rha; Byoung Geol Choi; Jae Kyeong Byun; Se Yeon Choi; Jin Ah Cha; Soohyung Park; Kyuho Lee; Seungmin Back; Jieun Lee; Dong Oh Kang; Jah Yeon Choi; et al. (Indian Heart Journal, 2022)
Background: It has been reported that significant endothelial dysfunction or clinically evident vasospasm can be associated with drug-eluting stents (DESs). However, the impact of DES associated coronary artery spasm (CAS) on long-term clinical outcomes has not been fully elucidated as compared with those of patients with vasospastic angina. Methods: A total of 2797 consecutive patients without significant coronary artery lesion (<70%), who underwent the Acetylcholine (Ach) provocation test, were enrolled between Nov 2004 and Oct 2010. DES-associated spasm was defined as significant CAS in proximal or distal to previously implanted DES site at follow-up angiography with Ach test. Patients were divided into two groups (DES-CAS; n = 108, CAS; n = 1878). For adjustment, propensity score matching (PSM) was done (C-statistics = 0.766, DES-CAS; n = 102, CAS; n = 102). SPSS 20 (Inc., Chicago, Illinois) was used to analyze this data. Results: Baseline characteristics were worse in the DES-CAS group. After PSM, both baseline characteristics and the Ach test results were balanced except higher incidence of diffuse CAS and ECG change in the DES-CAS group. During Ach test, the incidence of diffuse spasm (93.1% vs. 81.3%, p = 0.012) and ST-T change (10.7% vs. 1.9%, p = 0.010) were higher in the DES-CAS group. At 3-year, before and after adjustment, the DES-CAS group showed a higher incidence of coronary revascularization (9.8% vs. 0.0%, p = 0.001), recurrent chest pain requiring follow up coronary angiography (CAG, 24.5% vs. 7.8%, p = 0.001) and major adverse cardiac events (MACEs, 9.8% vs. 0.9%, p < 0.005). Conclusion: In this study, DES associated CAS was associated with higher incidence of diffuse spasm, ST-T change and adverse 3-year clinical outcomes. Special caution should be exercised in this particular subset of patients.